Features of state regulation of gold mining in the Kyrgyz Republic - Kh. B. Monakhova (Nomadic Civilization: Historical Research)
Precious metals are an important element of the global economy and are of strategic importance for many countries. The Kyrgyz Republic, located in Central Asia, has significant reserves of precious metals, including gold, silver and platinum. The gold mining industry is one of the key sectors for the economy of the republic, providing a significant part of the country’s non-metallic resources, and is one of the main investment objects for both local and foreign investors. Therefore, the development of the gold mining industry is important not only to ensure the economic stability of the country, but also to solve the socio-economic problems of the population throughout Kyrgyzstan. This article examines the specifics of state regulation of the gold mining industry, including licensing and control over the legality of mining. The article analyzes the legislative framework governing the activities of gold mining in the country, highlights the basic principles and mechanisms of state control over this industry, assesses the impact of regulation on the country’s economy and offers recommendations for improving the system of state regulation. In general, the article provides an overview of the current state of gold mining in the Kyrgyz Republic and its regulation, and also contains recommendations for improving the situation in this area.